Non-audit services and auditor independence in Malaysia : knowledge spillover in construction companies / Wan Zurina Nik Abdul Majid, Marziana Madah Marzuki and Muhammad Amiruddin Azizi Salleh - Nik Abdul Majid, Wan Zurina; Marzuki, Marziana Madah (2021)
The study examines the relationship between non-audit services (NAS) and auditor independence in construction companies in Malaysia. The study also considers other control variables that contribute to the independence of auditor such as leverage, big4, loss, family firm, auditor ethnicity, capital intensity, audit fee and audit committee independence. The study employs descriptive analysis, univariate tests and multivariate regression to investigate the potential effect of NAS on auditor independence. The data for NAS and other control variables were hand collected from annual reports downloaded from Bursa Malaysia's website. Based on 147 firm-year observations from construction companies for the period 2017-2019, the study found that the joint produce of audit and NAS did not compromise auditor independence. This empirical result failed to prove the economic bond created between auditors and clients that restricted the auditors from performing their duty objectively. The finding supports the argument of knowledge spillover in which while doing audit, the auditor gains experience and yield audit efficiency. These results contribute to Malaysia's policy deliberation to account for the effects of NAS on auditor independence using the direct method of audit opinion. This study contributes to theoretical perspectives on knowledge spillover which is very limited in Malaysia